The Elements of the Mechanism of Improving the Efficiency of the Enterprise’s Financial Potential - Zhytar Maksym O.; Yarova Lina S. (Bìznes Inform, 2020)
The article is aimed at developing both the elements of mechanism and the ways to increase the financial potential of enterprise on the basis of an analysis of theoretical approaches to the essence and components of the financial potential of enterprise in market conditions. It is proved that the globalization of the world economy, the instability of the political and economic situation in the State, high international requirements for the quality of products in recent years have had a negative impact on the enterprises of the State. It is substantiated that in the conditions of rapid development of the market economy, the main task of any economic entity is to achieve and ensure its own financial stability. Conclusions have been drawn that innovation potential increases the financial potential by introducing new energy-saving technologies, environmentally friendly technologies, new approaches to the organization of labor economy; increasing the competence of employees; development of dietary and high-quality products (for food enterprises). The investment potential is able to increase the financial potential as follows: to invest in social projects and programs, in the development of new technologies and innovation-production activities; to conduct charitable activities. The information potential will be able to increase the financial potential in the following ways: to act as a supporter of the policy of European values of doing business; to conduct marketing policy in accordance with current social, innovative and environmental trends; to ensure the level of maximum openness.